Plasma insulin and lipid levels in untreated obstructive sleep apnoea and snoring; their comparison with matched controls and response to treatment. - Davies, R; Turner, R; Crosby, J; Stradling, JR (1994)
Obstructive sleep apnoea (OSA), and snoring are associated with coronary heart disease. To assess whether OSA or snoring may contribute to this by raising fasting lipid or insulin levels, venous fasting total cholesterol, triglyceride, very-low-density lipoprotein, low-density lipoprotein, high-density lipoprotein, and insulin were measured in 15 untreated OSA patients and 18 snorers. Each of these subjects was individually matched to a control of the same sex, age +/- 10%, body index +/- 15%, smoking and drinking habits. This produced study groups which did not differ significantly by any of these criteria. Fasting venous blood samples were collected at 06.30 hours following polysomnography, and analysed blind of the subjects respiratory status. The OSA patients were then treated with nasal continuous positive airway pressure. In 10 of these subjects lipid and insulin levels were repeated after more than three months treatment. Lipid and insulin levels were also remeasured in the controls matched to these 10 subjects. The end points were compared with paired t-tests. There was no difference in any of the end points when the untreated OSA patients and the snorers were compared to their matched controls (P > 0.25 for all comparisons), and none of the indices changed when OSA was corrected with nasal continuous positive airway pressure (P > 0.25 for all comparisons). Patients with obstructive sleep apnoea or snoring do not have significant fasting hyperlipidaemia or hyperinsulinaemia when compared to carefully matched controls. These factors are therefore unlikely to be the cause of the excess cardiovascular mortality experienced by this patient group.